Incidence of the senses in motivation to children's writing - Acero-Verdugo, Germán; Salazar-Campos, Héctor Leandro; García-López, Héctor (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This document presents the advances of a research that seeks to surpass the attitudes of indifference and little interest shown by students when writing a text. This study was conducted with 68 students from grades 302 and 503 of the Instituto Técnico Industrial Rafael Reyes of Duitama, who have ages ranging from 8 to 10 years. It was used a qualitative methodology focused on the educational action research model and developed in the phases of planning, action, observation and reflection. The techniques and instruments used were observation, questionnaire, interview, and field diary. The results were analyzed in a triangulation process. For this research was designed a series of didactic workshops, taking as a motivating element the use of the senses and its incidence in children's writing. The research allows conclude that the senses are underdeveloped in the students and that their exploration in the school environment motivates and enriches even more the written productions.